2019
DOI: 10.1042/bsr20190590
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of lncRNAs in regulating cancer cell radiosensitivity

Abstract: Radiotherapy is one of the main modalities of cancer treatment. However, tumor recurrence following radiotherapy occurs in many cancer patients. A key to solving this problem is the optimization of radiosensitivity. In recent years, long non-coding RNAs (lncRNAs), which affect the occurrence and development of tumors through a variety of mechanisms, have become a popular research topic. LncRNAs have been found to influence radiosensitivity by regulating various mechanisms, including DNA damage repair, cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…[ 9 ] In recent years, series of radioresistance‐associated lncRNAs (e.g., HOTAIR, BOKAS, and lncRNA‐p21) have been reported and regulating their expression can induce multiple biological changes, such as blockage of DNA damage repair and promotion of apoptosis. [ 12,35 ] Genome‐wide analysis has shown that a large fraction of the human genome (≈98%) cannot encode proteins but can be transcribed into “non‐coding RNAs” that may exert their biological functions. [ 13 ] Therefore, the number of currently identified radioresistance‐associated lncRNAs is still very low and much more efforts need to be made to discover new functional lncRNAs and elucidate their regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] In recent years, series of radioresistance‐associated lncRNAs (e.g., HOTAIR, BOKAS, and lncRNA‐p21) have been reported and regulating their expression can induce multiple biological changes, such as blockage of DNA damage repair and promotion of apoptosis. [ 12,35 ] Genome‐wide analysis has shown that a large fraction of the human genome (≈98%) cannot encode proteins but can be transcribed into “non‐coding RNAs” that may exert their biological functions. [ 13 ] Therefore, the number of currently identified radioresistance‐associated lncRNAs is still very low and much more efforts need to be made to discover new functional lncRNAs and elucidate their regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, series of functional lncRNAs have been identified as key factors to induce radioresistance by regulating the expression of target genes at transcriptional or post‐transcriptional levels. [ 11,12 ] Although the regulatory mechanisms of these lncRNAs have been extensively elucidated, their clinical translation is significantly hindered because few efforts have been focused on developing effective in vivo delivery strategies to regulate the biological functions of lncRNAs. In addition, compared to the billions of intracellular lncRNAs that may exert their biological functions, [ 13 ] the proportion of currently discovered radioresistance‐associated lncRNAs is still very low and thus more functional lncRNAs and their regulatory mechanisms need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that lncRNAs regulate the radiosensitivity of cancer cells, including HCC cells. 9 For instance, NEAT1_2 depletion enhanced HCC cell radiosensitivity by modulating miR-101-3p and repressing WEE1. 24 Additionally, lncRNA H19 triggered the radioresistance of HCC cells by acting as a ceRNA for miR-193a-3p and upregulating PSEN1.…”
Section: Discussionmentioning
confidence: 99%
“…8 Besides, more and more investigations have manifested that lncRNAs exert a vital effect on the radiosensitivity of tumor cells by functioning as competing endogenous RNA (ceRNA). 9 For example, PTPRG-AS1 facilitates radioresistance in nasopharyngeal carcinoma by sponging microRNA-194-3p and increasing PRC1 expression. 10 Besides, LINC00483 silencing potentiates radiosensitivity in lung adenocarcinoma by regulating the microRNA-144/ HOXA10 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative radiotherapy is one of the main modalities of GBM treatment, but it often fails to achieve the expected results mainly due to tumor radioresistance. Increasing studies showed that lncRNAs have been found to modulate radiosensitivity by regulating various mechanisms [27].Wang et al reported that lncRNA PVT1 served an oncogenic role and played an important role in radiosensitivity in malignant nasopharyngeal carcinoma via activating the KAT2A acetyltransferase and stabilizing HIF-1α [28]. Another study suggested that lncRNA TP73-AS1 was highly expressed in hepatocellular carcinoma and participated in radioresistance via PTEN/AKT signaling pathway [29].…”
Section: Discussionmentioning
confidence: 99%